2020
DOI: 10.25217/ji.v5i1.576
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Education Based on Arabic Pegon Letters in Madrasah Diniyah Al Barokah Watuagung Tambak Banyumas

Abstract: This article aimed to analyze the Islamic education based on Pegon Arabic letters in Madrasah Diniyah Al-Barokah Watuagung. This research was qualitative research. Observation, interview and documentation were collecting data of research. The participants consist of 30 students and 5 teachers as research sample. The results showed that Madrasah Diniyah Al-Barokah used the Arabic letters Pegon in learning. This Madrasah still exists amid the vortex of globalization to preserve the legacy of civilization for sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
0
0
1
Order By: Relevance
“…This will greatly affect students' understanding of the meaning and values contained. 30 The Impact of the Utawi Iki-Iku (Pegon Symbols) Formula Method in…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will greatly affect students' understanding of the meaning and values contained. 30 The Impact of the Utawi Iki-Iku (Pegon Symbols) Formula Method in…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Each symbol represents a specific syntactic structure such as subject, predicate, time description, object, and so forth. 12 According to a study initiated by Bolgun, it was found that teaching Foreign Grammar (nahw) directly or in its original form can be an effective way of learning. This method also has a positive impact on the learners' abilities to achieve a high level of language proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Tradisi pesantren dengan kajian arab pegon dan pengamalan akhlak telah berkontribusi besar dalam penyebaran islam di Indonesia. Implikasi dari pesantren lahir wajah wajah muslim yang ramah berbudaya, berilmu, cinta damai yang menghantarkan kerukunan baik sesama manusia maupun antar umat beragama, memiliki karakter yang tidak hanya masalah teknis dan pragmatis belaka melainkan mengandung unsur kepentingan sosial dan mengkonfirmasi keragaman tradisi dan budaya di Indonesia (Ulyan et al, 2020). Sistem pembelajaran seperti inilah yang akan dipadukan dalam program kegiatan di Ma'had al-Jami'ah.…”
Section: Eksistensi Ma'had Al-jami'ahunclassified